2021
DOI: 10.3389/fcvm.2021.700169
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Selected Cardiovascular Biomarkers in Takotsubo Cardiomyopathy and the Most Frequent Cardiomyopathies

Abstract: Introduction: Among the causes of de novo diagnosed cardiomyopathy, Takotsubo cardiomyopathy (TTC) plays a minor role, with an occurrence of 50,000–100,000 cases per annum in the United States. In clinical practice, a differentiation of a TTC toward an ischemic cardiomyopathy (ICMP) or a dilatative cardiomyopathy (DCMP) appears to be challenging, especially in a subacute setting or in atypical types of TTC.Methods: To investigate this issue, we analyzed serum levels of sST2, GDF-15, suPAR, HFABP, and clinical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 50 publications
1
4
0
Order By: Relevance
“…This aligns with previous findings indicating that inflammation and oxidative stress play significant roles in the pathogenesis of takotsubo cardiomyopathy (TTC) [42,43]. GDF-15 exhibited the highest levels in takotsubo cardiomyopathy (TTC) compared to ischemic cardiomyopathy (ICMP), dilated cardiomyopathy, the combined group of ICMP [37], and ACS [44], indicating its potential value in differential diagnosis.…”
Section: Growth/differentiation Factor-15 (Gdf-15)supporting
confidence: 91%
See 2 more Smart Citations
“…This aligns with previous findings indicating that inflammation and oxidative stress play significant roles in the pathogenesis of takotsubo cardiomyopathy (TTC) [42,43]. GDF-15 exhibited the highest levels in takotsubo cardiomyopathy (TTC) compared to ischemic cardiomyopathy (ICMP), dilated cardiomyopathy, the combined group of ICMP [37], and ACS [44], indicating its potential value in differential diagnosis.…”
Section: Growth/differentiation Factor-15 (Gdf-15)supporting
confidence: 91%
“…Interestingly, in a relatively small study, it was observed that the highest plasma levels of H-FABP were found in patients with dilated cardiomyopathy (DCMP), followed by levels in patients with ischemic cardiomyopathy (ICMP), and with a significant difference, lower levels were seen in patients with takotsubo cardiomyopathy (TTC). This finding suggests a potential clinical utility of H-FABP as a marker for distinguishing between DCMP and TTC [37]. Given that myocardial stunning is the underlying pathogenesis in takotsubo cardiomyopathy (TTC), it appears that TTC patients exhibit lower levels of myocardial stress compared to clinically compensated dilated cardiomyopathy (DCMP) patients [41].…”
Section: Heart-type Fatty Acid Binding Protein (H-fabp)mentioning
confidence: 95%
See 1 more Smart Citation
“…Life-threatening ventricular arrhythmias are observed in 8.6% of TTS patients. Left ventricular wall rupture, cardiogenic shock, and thrombosis are also reported [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…TTC predominantly affects postmenopausal women and is usually triggered by physical or emotional stress factors. The left ventricle typically demonstrates apical ballooning and basal hypercontractility but also midventricular, basal, as well as focal left ventricular contractile abnormalities can be seen [ 3 ]. Inflammation, sympathetic overdrive-mediated multi-vessel epicardial spasms, microvascular dysfunction, and direct toxicity of catecholamines have been proposed as pathophysiological mechanisms [ 4 ].…”
Section: Introductionmentioning
confidence: 99%